RAMUAN HERBAL ALAMI YANG AMAN UNTUK ANAK SEBAGAI ALTERNATIF PENURUN DEMAM DAN PEREDA BATUK PILEK - Suhartini; Sukirawati; Djajanti, Agust Dwi; Thahir, Zakiah; Basir, Hernawati (Akademi Farmasi Yamasi Makassar, 2023)
Children who experienced cases of acute kidney failure or AKI (acute kidney injury) between the end of August and the beginning of October 2022 in 27 provinces in Indonesia were the victims of the quality of the drug syrup product in a thorough manner, through risk-based sampling and testing, which started with the development of analytical methods EG/DEG contamination testing on finished products. Tests on solvent raw materials suspected of containing EG/DEG beyond the allowable limits were conducted, and it was discovered that EG/DEG that above the threshold might result in acute kidney failure. This is what makes people afraid to give children syrup concoctions that contain chemical medications. To convince the public of the efficacy and safety of herbal concoctions made from medicinal plants found all around us to be used as fever medicine and cough medicine for children, we hope to be able to explain through education that there are alternative herbal remedies that can be used to overcome the events that occurred. inexpensive, hygienic, and simple to prepare. The activity is conducted in the form of counseling and the showing of instructional videos on how to prepare herbal remedies for children's fever, cough, and flu. PKM events were successful and met with enthusiasm positive reaction from the locals of Sombalabella Village, Pattalassang District, Takalar Regency, as shown by the fact that after receiving education, their level of knowledge rose from 65% to 74.2%.